The genus Plectrocnemia Stephens in China (Trichoptera, Polycentropodidae) - Zhong, Hua; Yang, Lian-Fang; Morse, John C. (Zootaxa, 2012)
Currently, 21 species of the genus Plectrocnemia are known from China. Examination of material collected from 13 provinces of China from 1990–2005 has revealed 9 new species and 3 new records of this genus, bringing the number of Chinese Plectrocnemia species to 33. Newly described species include: P. monacanthus sp. nov., P. huangi sp. nov., P. maoerensis sp. nov., P. pectinata sp. nov., P. fanjingensis sp. nov., P. platilobus sp. nov., P. paragryphalis sp. nov., P. bifoliolata sp. nov., and P. wuyiensis sp. nov. Two species, Plectrocnemia sinualis Wang & Yang and P. uncata Wang & Yang are synonymized with P. tsukuiensis (Kobayashi) and P. tortosa Banks, respectively. Plectrocnemia jonam (Malicky), P. ondakeana Tsuda and P. salah Malicky are newly recorded for the Chinese fauna. All species are organized by monophyletic species groups; the diagnostic characters for the species groups are discussed.